A Model of Economic Growth with Induced Bias in Technical Progress - Chang, Winston W. (Review of Economic Studies, 1972)
Journal Article A Model of Economic Growth with Induced Bias in Technical Progress Get access Winston W. Chang Winston W. Chang State University of New York at Buffalo Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 39, Issue 2, April 1972, Pages 205–212, https://doi.org/10.2307/2296872 Published: 01 April 1972